2019
DOI: 10.21608/eos.2019.77630
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the efficacy of Regenamel in the treatment of white spot lesions: an in vitro study

Abstract: Objective: The aim of this study was to evaluate the efficacy of REGENAMEL® on white spot lesions (WSLs)in terms of the extent of color change and the degree of mineralization.Materials and methods: Artificial white spot lesions were induced in 40 extracted human premolars, divided into a test and a control groups. REGENAMEL® was applied to the test group according to manufacturer's instructions, while the control group received no treatment. Both groups were incubated in remineralizing solution for 90 days at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…However, the control group showed there has been no major change in morphology in both 1 week and 4 weeks. Also, Hany et al, (11) who claimed that a considerable difference existed between the Selfassembling peptide P11-4 and the control group that received no treatment when comparing the color change after 90 days. Riad et al, (12) also found that there was a better color change after application of Self-assembling peptide P11-4 in treatment of white spot lesion.…”
Section: Discussionmentioning
confidence: 99%
“…However, the control group showed there has been no major change in morphology in both 1 week and 4 weeks. Also, Hany et al, (11) who claimed that a considerable difference existed between the Selfassembling peptide P11-4 and the control group that received no treatment when comparing the color change after 90 days. Riad et al, (12) also found that there was a better color change after application of Self-assembling peptide P11-4 in treatment of white spot lesion.…”
Section: Discussionmentioning
confidence: 99%